2016
DOI: 10.14744/anatoljcardiol.2015.6639
|View full text |Cite
|
Sign up to set email alerts
|

Relationship between platelet-to-lymphocyte ratio and the presence and severity of coronary artery ectasia

Abstract: Objective:The aim of this study was to investigate the relationship between platelet-to-lymphocyte ratio (PLR), an easily available inflammatory marker, and coronary artery ectasia (CAE).Methods:After applying the exclusion criteria, the retrospective study population consisted of 330 patients, including 110 patients with isolated CAE, 110 with obstructive coronary artery disease (CAD), and 110 with normal coronary artery angiograms (NCA). The severity of isolated CAE was determined according to the Markis cla… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
16
1
4

Year Published

2017
2017
2020
2020

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 14 publications
(24 citation statements)
references
References 25 publications
3
16
1
4
Order By: Relevance
“…Recently, increased PLR and decreased LMR have been reported to be associated with disease activity in many diseases. [ 33 37 ] But they could not show these correlations with other inflammatory marks such as hs-CRP or ESR. These serum inflammatory parameters can be considered as appropriate, confirmatory tests for hs-CRP and ESR.…”
Section: Discussionmentioning
confidence: 99%
“…Recently, increased PLR and decreased LMR have been reported to be associated with disease activity in many diseases. [ 33 37 ] But they could not show these correlations with other inflammatory marks such as hs-CRP or ESR. These serum inflammatory parameters can be considered as appropriate, confirmatory tests for hs-CRP and ESR.…”
Section: Discussionmentioning
confidence: 99%
“…In recent years, PLR, derived from platelet and lymphocyte counts and indicated as a useful indicator of systemic inflammatory response, was firstly used as a prognostic marker of some oncological diseases [20][21][22]. Then, this marker was shown to be associated with inflammation in cardiovascular diseases [11][12][13][14][15]. In addition, PLR has been reported to correlate with other inflammatory markers such as CRP and fibrinogen, which have proven to be predictive and prognostic in cardiovascular disease [23].…”
Section: Discussionmentioning
confidence: 99%
“…Low blood lymphocyte count has been shown to be associated with poor cardiovascular outcomes in coronary artery disease (CAD) [9,10]. Platelet-to-lymphocyte ratio (PLR), derived from these values, is a useful parameter showing the degree of the inflammatory response, which is used as an important prognostic factor in many cardiovascular diseases [11][12][13][14][15]. In our previous study, we showed that high PLR levels in patients with ACS increase in-hospital mortality [12].…”
Section: Introductionmentioning
confidence: 99%
“…First described in 1967 as an indicator of ozone exposure, 10 NLR has shown prognostic value in different cardiovascular conditions including stable coronary artery disease, acute coronary syndromes, HF, and coronary artery bypass grafting (CABG). 11 On the other hand, platelet-to-lymphocyte ratio (PLR) was first described in 2008 as a prognostic marker in periampullary cancer 12 and has also shown prognostic value in patients with ST elevation acute myocardial infarction [13][14][15] and stable coronary artery disease 16,17 and in patients with an implantable cardioverter defibrillator. 18 Despite raising evidence supporting the use of NLR and PLR in cardiovascular disease, no study has evaluated the role of these markers in patients undergoing HTX.…”
Section: Introductionmentioning
confidence: 99%